2014
DOI: 10.1007/s12633-014-9264-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Materials Based on Fluorocarbofunctional Spherosilicates

Abstract: Consecutive hydrosilylation-based syntheses were performed of silsesquioxanes containing mixed groups 1H,1H,2H,2H-perfluorooctyl (PFD) or octafluoropentyloxypropyl (OFP) and trimethoxysilylethyl (TMS) in different stoichiometric ratios. The presence of TMS makes it possible to form covalent bonds with substrates due to the reactivity of this group. All obtained derivatives were applied to hydrophobization of glass plates and by comparison of water contact angles (WCA) on modified surfaces the effect of silsesq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…The latter groups can react with surface hydroxyl groups and, moreover, due to their longer chain (compared to trialkoxysilyl group present in the derivatives 1-3) they can cause a greater surface diversification [45,46]. The most likely reason for this disparity is the different nature of surface hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter groups can react with surface hydroxyl groups and, moreover, due to their longer chain (compared to trialkoxysilyl group present in the derivatives 1-3) they can cause a greater surface diversification [45,46]. The most likely reason for this disparity is the different nature of surface hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrosilylation was carried out with two pairs of olefins: 1,1,2,2,3,3,4,4-octafluoropentyl allyl ether and vinyltrimethoxysilane, as well as 1,1,2,2,3,3,4,4-octafluoropentyl allyl ether and glycidyl allyl ether, according to the procedure reported in the literature [44,45]. Two families of derivatives have been obtained in which the ratios of respective functional groups were 7:1 (the derivatives 1 and 2 containing fluoroalkyl and trimethoxysilyl or glycidoxypropyl groups, respectively) and 4:4 (the derivatives 3 and 4, containing fluoroalkyl and trimethoxysilyl or glycidoxypropyl groups, respectively).…”
Section: Synthesis Of Bifunctional Silsesquioxanesmentioning
confidence: 99%
See 1 more Smart Citation
“…1), but only a few previous studies have described cage molecules containing 4, 6, 10, or 12 silsesquioxane fragments. By contrast, over 1000 previous studies have reported octameric cage molecules [RSiO 1.5 ] 8 (cubic structures) with different organic groups at the silicon atom [2,[11][12][13][14][15][16][17][18][19][20][21][22] (see Table 1). M a n u s c r i p t 3 This prevalence of octameric structures among structures with the same composition but different sizes is not accidental, and there are several possible explanations.…”
Section: Introduction Of Metal Atoms Into Cage Siloxane Structurementioning
confidence: 99%
“…These compounds, when applied to the modification of glass, made it possible to create superhydrophobic coatings (Maciejewski et al 2014a(Maciejewski et al , b, 2015. However, in the case of glass surfaces and glass fibers (as well as mineral fibers), alkoxy groups easily undergo condensation due to the different character of the Si-OH groups on glass surfaces in contradistinction to the C-OH groups present on surfaces of natural fibers (Valdez-Gonzalez et al 2009).…”
Section: Introductionmentioning
confidence: 99%